From Daughter to Soldier: Analysis of Gender Subversion in Mulan Comic through Judith Butler’s Feminism - Johanes, Cayla Abielle; Manurung, Asti Thesalonika; Axell Kyrie; Sitompul, Darrell Timothy; Hutapea, Justin Tio Manuel (Jurnal Pendidikan Makarios, 2025)
This study explores how gender identity informs female empowerment in the comic book Mulan (2020), analyzed through Judith Butler’s theory of Gender Trouble: Feminism and the Subversion of Identity (1990). Using a qualitative approach, the research examines both extrinsic elements (visual style, dialogue bubbles, and coloring techniques) and intrinsic aspects (plot, character development, and themes). The analysis reveals the findings. 1) Mulan’s struggles are framed by traditional Chinese values of devotion and duty, which she redefines against patriarchal constraints. 2) The comic employs themes of resilience and transformation, portraying Mulan’s resistance to restrictive gender norms. 3) Mulan’s journey illustrates that gender roles are not inherently tied to masculinity or femininity, but can be subverted to embrace autonomy and self-worth. These findings highlight the relevance of children’s comics as cultural texts that challenge stereotypes and highlight social issues, offering readers a deeper understanding of gender, empowerment, and identity.